Dietary patterns of Sonoran breastfeeding women are associated to exclusive or partial breastfeeding regimes - Alejandra Arguelles-López; Omar A. Trujillo-Rivera; Ana M. Calderón- (Permanyer, 2024)
Background: During breastfeeding, the maternal diet ensures mothers and infants health. Therefore, it is necessary to update information about the diet of exclusively or partially breastfeeding women in each population. We evaluated the diet of Sonoran breastfeeding women, identified their dietary patterns, and examined their association with the breastfeeding regime. Methods: In this cross-sectional study, 62 women breastfeeding exclusively (n = 43) or partially (n = 19) participated. The diet was assessed using a food frequency questionnaire, and patterns were identified through principal component analysis. Results: Overall, fats and sodium intake were higher, while potassium intake was lower than recommended. Two dietary patterns were identified: "regional" (n = 36) and "prudent" (n = 26). Women following the "prudent" pattern consumed more protein, calcium, and potassium than those following the "regional" pattern (p < 0.05). The probability of exclusively breastfeeding women having a "prudent" dietary pattern was higher than that of partially breastfeeding women (adjusted odds ratios = 7.29, p = 0.019). Conclusions: Exclusive breastfeeding possibly motivated mothers to follow a more prudent diet than those who partially breastfed. Therefore, it is crucial to promote a healthy diet among breastfeeding mothers.